Historical and comparative perspectives on trade union regulation with specific emphasis on the accountability of trade unions to their members - Greenhalgh, Bradley Paul (Stellenbosch University, 2020)
How do members hold their own trade unions accountable in South Africa? What legal mechanisms, if any, are available to assist union members in receiving adequate representation and service from their unions? This study approaches these questions through a comparative and historical examination of the regulation of the union member relationship in the UK, USA and the RSA. The study commences with an examination of what unions do, how they function and what benefits potentially accrue to their members, while the role played by unions in utilising collectivisation to offset the bargaining power of employers is demonstrated. The need for organised labour, by society in general, but South Africa specifically, is brought into sharp relief. This is, however, offset by the examination of 25 constitutions of broadly representative South African trade unions, where the lack of proper regulation of the union-member relationship is brought to the fore. This already means the common law and current judicial approach that is so reliant on the interpretation and implementation of trade union constitutions to address union-member disputes is unsuitable, certainly in those instances where the constitution is either silent or ambiguous, or where the nature of the relationship between the union and its member(s) mimics that of the constantly present imbalance of power and influence between employers and employees. The comparative examination of union accountability is undertaken against the backdrop of the common historical phases of proscription, acknowledgement/assimilation, and readjustment of and towards trade unions. The historical and contemporary regulation of the union-member relationship in South Africa is examined in the same way. The study demonstrates that purely statutory regulation of the union member relationship by means of punitive provisions and inter-union self-regulation measures are not feasible. A series of possible legal mechanisms – that draw from the comparative examination – are suggested, even though they are to be utilised in a collective (rather than individual) way. Even these suggestions, however, are subject to the challenges of cost-effectiveness, accessibility and efficiency of enforcement by (the) average union member(s). Three proposals are made to foster improved union member accountability: Firstly, the use of section 103A of the LRA by the Registrar so as to place unions that meet the appropriate criteria under administration, in order to restore accountable functioning and elevate the interests of the member(s) over that of the officials of the union; secondly, the introduction of a duty of fair representation – to be administered by the CCMA – to hold both union and employer accountable to members, and; thirdly, in conjunction with the first two proposals, the use of a package of further measures (and an associated information campaign), such as bolstering the financial/institutional capacity of the Registrar’s office, compelling the inclusion of accountability clauses within union constitutions, and minor amendments to the LRA with regard to balloting, reporting/transparency (and the enforcement thereof). If implemented, the expected outcomes are improved labour relations, increased accountability and professionalisation of trade union administration, a realignment of the employer-union divide and elevating the awareness of union member rights and concomitant obligations on trade unions – all of which are of critical importance in South Africa’s post-Marikana society.
URI: http://hdl.handle.net/10019.1/109343
Keywords: Labor union members; South Africa; Trade union accountability; Union security

An economic and legal analysis of trade measures against illegal, unreported and unregulated fishing - Ma, Xuechan (Marine Policy, 2020)
Illegal, unreported and unregulated (IUU) fishing threatens the ability of the aquatic systems to continue providing vital ecosystem services and essential food resources. Most of the existing economic analysis on IUU fishing is conducted from the perspective of IUU fishing vessels rather than that of States. This paper seeks to fill this gap and concludes that trade measures against IUU fishing are cost-effective for the international community, as the IUU fishing has reached such a substantial scale that the total harm or loss caused is estimated to be greater than the total abatement costs required. Meanwhile, from a legal point of view, trade measures against IUU fishing might have more tensions with international trade law than with the international law of the sea. This paper draws on relevant GATT and WTO jurisprudence for guidance to eliminate such tensions. Two other comprehensive solutions to ensure legal compliance of trade measures against IUU fishing include taking such measures on a cooperative basis and making use of the standard-setting process through competent international organizations or conferences such as the FAO.
Keywords: Economic analysis; IUU fishing; International trade law; The law of the sea; Trade measures

The African Continental Free Trade Area: Toward a New Legal Model for Trade and Development - Kuhlmann, Katrin; Agutu, Akinyi Lisa (Georgetown Journal of International Law, 2020)
International trade law is at a turning point, and the rules as we know them are being broken, rewritten, and reshaped at all levels. At the same time that institutions like the World Trade Organization (WTO) face significant change and a global pandemic challenges the rules of the market, Africa’s new mega-regional trade agreement, the African Continental Free Trade Area (AfCFTA), is emerging as a promising framework for redesigning international economic law. As this Article will argue, the AfCFTA presents a new normative approach to trade and development that is positioned to rewrite the rules in a more inclusive and equitable way and, over time, possibly affect global trade well beyond the African continent.Historically, trade and development have been linked through the framework of Special and Differential Treatment (S&D), which has been a central feature of the WTO and is increasingly shaping regional trade agreements (RTAs) as well. Although the connection between trade and development is more important than ever before, traditional S&D is not positioned to deliver on broader priorities of social and economic development in the current international climate. Fortunately, as this Article will argue, Africa’s approach under the new AfCFTA sets the stage for a needed refresh of S&D. While the AfCFTA incorporates traditional aspects of S&D, it also includes elements of a forward-looking, rules-based approach to further economic and social development, advancing the Sustainable Development Goals (SDGs). This new dimension of S&D holds great potential for promoting integration through trade, representing the needs of a diverse group of countries in the rulemaking process, and reshaping international economic law more broadly to generate positive development outcomes. This Article begins with an assessment of the AfCFTA as an alternative model for trade and development law, evaluating the agreement in the historical and evolving context of S&D and examining its role in shaping a new normative approach to S&D. The AfCFTA, we argue, represents a shift from using S&D as a largely defensive trade approach to one that positions S&D as an affirmative tool for achieving sustainable development through the design and implementation of the rules of trade themselves, while still maintaining flexibility for countries that need it. This new approach may finally replace the old trade paradigm of the ”haves and have nots” with a system in which trade rules can be designed to benefit all. Although the AfCFTA is still at an early stage and will have to overcome formidable challenges, this Article provides an initial assessment of the AfCFTA’s proactive new model in the context of the substantive areas of law identified as next-stage (Phase II) negotiating priorities: intellectual property rights (IPR), investment, and competition law. The Article’s comparative assessment draws upon the laws of African nations, African and international RTAs, and other proposals for international legal reform. Finally, the Article looks to the future, positing that the AfCFTA could be the best legal instrument available to break the stalemate in international rulemaking, design new trade law approaches to pressing issues like global health and food security, and close the loop between trade rules and development goals, including the seventeen SDGs. As the AfCFTA is rolled out and implemented, it could have a profound impact on trade and development law, reshaping the rules for Africa and perhaps the world as well.
Keywords: AfCFTA; African Continental Free Trade Area; International Economic Law; International Trade

Trade in Services in the African Continental Free Trade Area: Prospects, Challenges and WTO Compatibility - Simo, Regis Yann (Journal of International Economic Law, 2020)
This article engages with the recently adopted agreement for the African Continental Free Trade Area (AfCFTA) in the area of services. While services trade had heretofore stood at the queue of African trade pacts, the AfCFTA breaks new grounds by negotiating goods and services concurrently, signalling a paradigm shift and a commitment to a deeper integration of the continent. Upon Members’ implementation of the Protocol on Trade in Services, whose aim is to establish a single market in services, the region will be the largest economic integration agreement ever concluded since the birth of the World Trade Organization (WTO). This paper sets out to analyse the provisions of the Protocol and how they contribute to achieving the objective of attaining a single market where services (alongside goods, people and capital) move unrestricted.

The regulation of international commercial arbitrators - Loreto Ilhao Moreira, João (University of Oxford, 2020)
International commercial arbitration has established itself as the main dispute resolution mechanism for international commercial disputes. This increased visibility has drawn attention to arbitrators’ public role, leading to a well-established general perception that arbitrators are bound to special obligations, such as the duty to be independent and impartial or the obligation to assure that arbitral proceedings are not abused to achieve nefarious goals. Despite this general acknowledgement, little attention has been paid to the mechanisms that ensure that arbitrators adhere to these obligations. In particular, there has been limited analysis of the underlying mechanisms that incentivise the production and enforcement of professional norms in this field. This thesis argues that the particulars of the arbitration market largely explains why the evolution of the regulation of international arbitrators has not matched those of other professions. At the same time, it will argue that those same particularities create incentives for several actors, most notably the arbitral community itself, to step in and occupy this regulatory vacuum. In particular, it explores the notion that the market strategies employed by arbitrators, arbitral institutions and other members of the arbitral community have the production of professional norms as a by-product. It further explores how the arbitral market tends to create an environment where compliance with professional norms is rewarded, leading, at the same time, the arbitral community to work as a network that promotes adherence to professional norms through mostly informal sanctions.
https://ora.ox.ac.uk/objects/uuid:c2dd717f-e53b-4ab6-b848-c089b70adec2
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration (international law); Arbitration market; Dispute Resolution; International commercial arbitrators; Regulation